2002
DOI: 10.1111/j.1432-2277.2002.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic blood perfusion of isolated rabbit kidneys. III. In vitro physiology of kidneys after perfusion with Euro-Collins solution or 7.5 M cryoprotectant (VS4)

Abstract: Cryopreservation of solid organs might be possible using a mixture of cell-permeable agents, cryoprotectants (CPA), which are designed to completely preclude ice crystal formation during cooling to cryogenic temperatures. The effects of a specific prototype solution (VS4) were evaluated by normothermic blood perfusion in vitro. Rabbit kidneys were divided into three groups: untreated controls (n = 7), Euro-Collins (EC)-perfused controls (n = 6) and VS4 (4970, w/v) CPA-perfused kidneys (n = 7). After a 2-h bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
3
1
1
Order By: Relevance
“…This is important as studies using a rabbit model demonstrated that weight gain closely paralleled impaired sodium and glucose tubular handling, and overall renal injury. Histological assessment showed this to be mainly interstitial fluid accumulation rather than cell swelling11. Despite this, the present findings provide further evidence for a vital role for leucocytes in early graft reperfusion injury that results in impaired renal function.…”
Section: Discussioncontrasting
confidence: 43%
“…This is important as studies using a rabbit model demonstrated that weight gain closely paralleled impaired sodium and glucose tubular handling, and overall renal injury. Histological assessment showed this to be mainly interstitial fluid accumulation rather than cell swelling11. Despite this, the present findings provide further evidence for a vital role for leucocytes in early graft reperfusion injury that results in impaired renal function.…”
Section: Discussioncontrasting
confidence: 43%
“…A number of experimental studies using rabbit, canine and porcine kidneys have suggested that normothermic renal resuscitation during organ preservation is more beneficial than traditional hypothermic techniques18–20. Although warm ischaemic injury and cold ischaemia can be controlled in the experimental setting20–23, in the clinical situation the logistics of organ retrieval and transfer necessitate a preliminary period of cold preservation averaging 16–18 h3.…”
Section: Introductionmentioning
confidence: 99%
“…Lower pressures have been chosen because of fears that preservation at physiological pressures could fail to maintain organ integrity and induce endothelial damage15, 17, 19. Higher, more physiological pressures have been used in other models to achieve better renal function, but at the expense of limiting the duration of perfusion to a matter of a few hours13, 14, 19, 20. Most previous investigators have not justified their choice of perfusion pressure or presented data relating to the effects of different pressures in the same model.…”
Section: Discussionmentioning
confidence: 99%
“…Normothermic organ preservation is more exacting than the more traditional hypothermic techniques and this is reflected in the variable success achieved using rabbit, dog and pig kidney models13–16. The optimal conditions under which to preserve kidneys normothermically remain undetermined.…”
Section: Introductionmentioning
confidence: 99%